2017
DOI: 10.1002/2016jd025287
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of a nonhydrostatic dynamical core in high‐resolution aquaplanet simulations

Abstract: This study explores the impact of a nonhydrostatic dynamical core in high‐resolution regional climate simulations using an aquaplanet framework. The Weather Research and Forecasting (WRF) model is used to conduct simulations with both hydrostatic (H) and nonhydrostatic (NH) solvers at horizontal grid spacings (Δx) of 36, 12, and 4 km. The differences between the H and NH simulated precipitation (ΔP) are notable even at Δx = 12 km in the intertropical convergence zone and the transition region to the drier subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 50 publications
5
29
4
Order By: Relevance
“…Also, consistent with Yang et al . [] who noted the importance of physics‐dynamics interactions in amplifying the difference between simulations with hydrostatic versus nonhydrostatic dynamical cores, our results show larger differences between H and NH at 36 km and 12 km resolution with the KF scheme compared to 4 km resolution without a cumulus scheme.…”
Section: Analysis Of Simulationsmentioning
confidence: 67%
See 2 more Smart Citations
“…Also, consistent with Yang et al . [] who noted the importance of physics‐dynamics interactions in amplifying the difference between simulations with hydrostatic versus nonhydrostatic dynamical cores, our results show larger differences between H and NH at 36 km and 12 km resolution with the KF scheme compared to 4 km resolution without a cumulus scheme.…”
Section: Analysis Of Simulationsmentioning
confidence: 67%
“…Consistent with Lebassi‐Habtezion and Diffenbaugh [] and Yang et al . [], nonhydrostatic dynamics has a positive impact on precipitation simulations over the western U.S. with complex terrain even at 12 km and 36 km grid spacings. The smaller differences between simulations with the hydrostatic versus nonhydrostatic dynamical core in this study compared to those in Lebassi‐Habtezion and Diffenbaugh [] are likely related to the different emphases on precipitation in the warm versus cold seasons.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, at increasingly finer grid‐spacing, hydrostatic models have been shown to exhibit divergent growth in the vertical velocity compared with nonhydrostatic models (Jeevanjee, ; Morrison, ; Weisman et al, ). Recent analyses by Yang et al () using both hydrostatic and nonhydrostatic formulations of the Weather Research and Forecasting (WRF) model at 36, 12, and 4 km showed statistically significant differences in simulated total precipitation in the tropics (largely due to latent heat release). However, differences within the midlatitudes were negligible between nonhydrostatic and hydrostatic simulations.…”
Section: Experimental Designmentioning
confidence: 99%
“…Previous studies have mostly been conducted to either focus on fine spatial resolution over short durations or long duration at a coarse resolution (Chen & Hossain, ; Hu et al, ; Leung & Qian, ). With advances in computing resources, convection permitting climate simulations at grid spacing of a few kilometers are becoming feasible and recent studies have demonstrated their usefulness for simulating cold season orographic precipitation and snowpack dynamics (Rasmussen et al, ) and extreme precipitation (Liu et al, ; Prein et al, ) as well as warm season precipitation and its diurnal variability (Gao et al, ; Prein et al, ; Yang et al, ). Overcoming the limitations of both model resolution and simulation period opens the door to improving analysis of AR events on climate time scale.…”
Section: Introductionmentioning
confidence: 99%